2016
DOI: 10.3906/vet-1502-68
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotics, organic acid, and a medicinal plant on the immune systemand gastrointestinal microflora in broilers challenged with Campylobacter jejuni

Abstract: Campylobacter jejuni, a zoonotic bacterial pathogen with worldwide distribution, infects about 400 million humans in the world annually. In order to reduce C. jejuni colonization in the gastrointestinal tracts of broilers and make chickens less susceptible to colonization, four commercial products based on organic acid, probiotics, and medicinal plants were used. In this experiment, 210 one-day-old male broiler chicks (Ross 308) were assigned to 7 treatment groups randomly with 3 replications and 10 birds in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Enzymes catalyzing digestive and absorptive functions seem to be spatially arranged in the brush border so as to offer a kinetic advantage for absorption, not only for digestive feedstuffs, but also for sodium, and possibly other ions by a mechanism of cooperative interaction between these and other absorbed molecules in the mobile carrier transport system ( Denbow, 2015 ). In addition, one could speculate that decrease of feed consumption in animals infected with pathogenic microorganisms such as Salmonella ( Rahimi et al, 2009 ) and Campylobacter ( Ebrahimi et al, 2016 ) could arise from damage to the intestinal mucosa that signals the neural center (hypothalamus) of the brain. A decrease in the intestine’s ability to take up specific nutrients, because of the lesions caused by pathogenic microorganisms, may play a role in the debilitation and wasting that often follows exposure to pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes catalyzing digestive and absorptive functions seem to be spatially arranged in the brush border so as to offer a kinetic advantage for absorption, not only for digestive feedstuffs, but also for sodium, and possibly other ions by a mechanism of cooperative interaction between these and other absorbed molecules in the mobile carrier transport system ( Denbow, 2015 ). In addition, one could speculate that decrease of feed consumption in animals infected with pathogenic microorganisms such as Salmonella ( Rahimi et al, 2009 ) and Campylobacter ( Ebrahimi et al, 2016 ) could arise from damage to the intestinal mucosa that signals the neural center (hypothalamus) of the brain. A decrease in the intestine’s ability to take up specific nutrients, because of the lesions caused by pathogenic microorganisms, may play a role in the debilitation and wasting that often follows exposure to pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The current results were consistent with those in the study by Oh et al [41], who found that supplementing broilers with probiotics reduced coliform and E. coli counts in Salmonella-challenged broilers. Ebrahimi et al [42] concluded that acidic pH from organic acids produced by supplementing broilers with PrimaLac ® (120 g/1 L water until the 14 th day, 454 g/1000 kg ration until the 28 th day, and 225 g/1000 kg ration for the rest of the growing period) reduced growth and colonization of Campylobacter jejuni. Nishiyama et al [43] and Saint-Cyr et al [44] reported that using Lactobacillus gasseri SBT2055 and Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Sigma Aldrich (Germany) supplied soybean lecithin with a purity of 99%. As a food-borne pathogen, C. jejuni (RTCC 1097) was provided from Razi Vaccine and Serum Research Institute, Karaj, Iran (Gharib Naseri et al, 2012;Ebrahimi et al, 2016). As part of the gene expression analysis, the RNeasy Mini kit from Qiagen (Hilden, Germany), SYBR Green PCR Master Mix from Qiagen (Hilden, Germany), cDNA Quantitect Reverse Transcription Kit (Qiagen, Hilden, Germany), and SYBR Green PCR Master Mix from Qiagen (Hilden, Germany) were utilised.…”
Section: Plant Materials and Reagentsmentioning
confidence: 99%
“…This experimental challenge was designed to determine the pathogenicity of C. jejuni, which was isolated from the cloaca of commercial broiler chicken (Gharib Naseri et al, 2012;Ebrahimi et al, 2016). The C. jejuni was propagated in microaerophilic conditions at 42 °C using selective culture media (Oxid, United Kingdom).…”
Section: Bacterial Preparationmentioning
confidence: 99%